OPEN DATA EN APLICACIONES MÓVILES: NUEVOS MODELOS PARA LA INFORMACIÓN DE SERVICIOi - Dr. Manuel GÉRTRUDIX BARRIO,Dr. Sergio ÁLVAREZ GARCÍA,Dr. Mario RAJAS FERNÁNDEZ (Fonseca, Journal of Communication, 2023)
The combination of open data generated by government and the proliferation of mobile devices enables the creation of new information services and improved delivery of existing ones. Significantly, it allows citizens access to simple, quick and effective way to information. Free applications that use open data provide useful information in real time, tailored to the user experience and / or geographic location. This changes the concept of “service information”.